Systemic Thinking Professional Teachers Learning Development - Baharuddin Baharuddin (Jurnal Sinestesia, 2022)
This research is aimed to develop the way of thinking system among Junior High School Students in Sidrap and Sinjai regencies, South Sulawesi province, Indonesia. The ability of the thinking system is mainly important for students in Indonesia since it may create skills to anticipate the global change. This research applied a qualitative description approach with literature study method, interviews and observations held in 5 schools. The result of this research shows that thinking system hasn’t yet been done properly because there are some obstacles such as incomplete curriculum and non-professional teachers. Based on the findings, schools need to have complete and proper curriculums, including improvement of the competence of professional teachers through training and education.